2020
DOI: 10.7150/jca.40196
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences and Adverse Effects between Chemotherapy and Immunotherapy for Non-Small Cell Lung Cancer

Abstract: Introduction: Lung cancer remains the leading cause of cancer mortality in men and women and around the world. Approximately 90% of cases of lung cancer are caused by smoking and the use of tobacco products. However, other factors such as asbestos, air pollution and chronic infections can contribute to pulmonary carcinogenesis. Lung cancer is divided into two broad histological categories, which develop and spread different small cell lung carcinomas and non-small cell lung carcinomas. The treatment options fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
(26 reference statements)
1
12
0
Order By: Relevance
“…The most common adverse event in the present study was CINV, in which vomiting was the most significant [n=17 (23.9%) in the control group; n=11 (20%) in the study group]. It has been previously reported that sex has a significant impact on adverse events induced by chemotherapy (16). Wheatley-Price et al found that female patients experienced more CINV compared with male patients (77% vs. 66%, P=0.0004) (17).…”
Section: Discussionsupporting
confidence: 43%
“…The most common adverse event in the present study was CINV, in which vomiting was the most significant [n=17 (23.9%) in the control group; n=11 (20%) in the study group]. It has been previously reported that sex has a significant impact on adverse events induced by chemotherapy (16). Wheatley-Price et al found that female patients experienced more CINV compared with male patients (77% vs. 66%, P=0.0004) (17).…”
Section: Discussionsupporting
confidence: 43%
“…The present study included only men. Sex disparities have been documented in lung cancer incidence [ 41 ] and sex may also influence treatment outcomes (such as in the case of epidermal growth factor receptor inhibitors and anti-programmed cell-death protein 1 (PD1) inhibitors) [ 42 ] or treatment complications [ 3 ]. Moreover, there are sex-related body composition [ 43 ] and PhA differences [ 28 ], and, possibly, sex differences in diet-related behaviors [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with non-small-cell lung cancer (NSCLC) represent the majority of lung cancer cases (~85%), while patients with the more aggressive small-cell lung cancer (SCLC) type represent ~10–15% of lung cancer cases [ 2 ]. The type of treatment seems to affect the undesirable effects of the treatment, with new therapeutic approaches, such as immunotherapy, being very promising [ 3 ]. One previous study in such patients revealed that a combined treatment of immunotherapy and chemotherapy acts effectively as it seems to prolong the survival rate [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The main treatments for lung cancer include chemotherapy, radiotherapy, surgery, targeted therapy, immunotherapy, and various clinical studies are ongoing research [ 6 11 ], which have brought a new revolution in the treatment of lung cancer but still limited. In some patients, underlying diseases may prevent clinical treatment from proceeding in full accordance with guideline recommendations, and these treatments may lead to unavoidable adverse events that may affect the quality of life of some patients [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%